Significance of research on natural products from marine-derived Aspergillus species as a source against pathogenic bacteria - Wang, Bin; Cai, Jin; Huang, Longtao; Chen, Yonghao; Wang, Ruoxi; Luo, Mengyao; Yang, Meng; Zhang, Mohan; Nasihat,; Chen, Guangying; Huang, Guolei; Zheng, Caijuan (Frontiers in Microbiology, 2024)
Bacterial infections posed a significant clinical burden on global health.The growing incidence of drug-resistant pathogens highlights the critical necessity to identify and isolate bioactive compounds from marine resources. Marine-derived fungus could provide novel lead compounds against pathogenic bacteria. Due to the particularity of the marine environment, Aspergillus species derived from marine sources have proven to be potent producers of bioactive secondary metabolites, and played a considerable role in advancing drug development. This study reviews the structural diversity and activities against pathogenic bacteria of secondary metabolites isolated from marine-derived Aspergillus species over the past fourteen years (January 2010-June 2024), and 337 natural products (including 145 new compounds) were described. The structures were divided into five major categories, terpenoids, nitrogencontaining compounds, polyketides, steroids, and other classes. These antimicrobial metabolites will offer lead compounds to the development and innovation of antimicrobial agents.